Solidarity, isolation, and cynicism: An attitudinal analysis of the police culture in the South African Police Service (The Strategic Review for Southern Africa, 2021)
Numerous scholars have contributed to the police culture body of knowledge (Cockcroft 2013; O’Neill, Marks & Singh 2007; Sklansky 2005). They submit that the traditional understanding of police culture is no longer relevant due to the new developments that have transpired in policing, which have consequently changed the police culture. More specifically, they suggest that the South African Police Service (SAPS) too has witnessed changes in the traits of its police culture that accentuate the cynicism of and isolation from the public. This article is an attempt to challenge this narrative by comparing the police culture themes of solidarity, isolation, and cynicism attitudes of two different cohorts of new South African Police Service (SAPS) recruits separated by ten years. By making use of the 30-item police culture themes of solidarity, isolation, and cynicism questionnaire, designed by Steyn (2005), the article establishes that a representative sample (138 out of a population of 140) of new SAPS recruits from the SAPS Chatsworth Basic Training Institute (August 2015), have remarkably similar attitudes in support of police culture themes of solidarity, isolation, and cynicism, compared to a representative sample of all new SAPS recruits that started their basic training in January 2005 (Steyn, 2005). Although small in representation, the study refutes the claims that traditional understandings of police culture are no longer relevant and that the traits of the police culture in the South African Police Service (SAPS) has so changed that it accentuates the cynicism of and isolation from the public.